Assessing collective affect recognition via the Emotional Aperture Measure. Issue 1 (2nd January 2016) - Sanchez-Burks, Jeffrey; Bartel, Caroline A.; Rees, Laura; Huy, Quy
Abstract : Curiosity about collective affect is undergoing a revival in many fields. This literature, tracing back to Le Bon's seminal work on crowd psychology, has established the veracity of collective affect and demonstrated its influence on a wide range of group dynamics. More recently, an interest in the perception of collective affect has emerged, revealing a need for a methodological approach for assessing collective emotion recognition to complement measures of individual emotion recognition. This article addresses this need by introducing the Emotional Aperture Measure (EAM). Three studies provide evidence that collective affect recognition requires a processing style distinct from individual emotion recognition and establishes the validity and reliability of the EAM. A sample of working managers further shows how the EAM provides unique insights into how individuals interact with collectives. We discuss how the EAM can advance several lines of research on collective affect.